The Structured Academic Controversy and its Influence on Communicative Self- Efficacy - Romero Meza, Alex Jhonatan (2025)
Self-efficacy in students plays an essential role in their integral development, both in their training and in the academic field, particularly in relation to the confidence they have in their own abilities to communicate orally in different social contexts. The present research aims to demonstrate that the cooperative strategy called Structured Academic Controversy (CAE) favors the development of communicative self-efficacy in students of secondary level of Regular Basic Education in Peru. For this, a study was carried out with a quasi-experimental design, considering a specific sample of students (n=58), to whom a survey was applied to measure their level of oral communicative self-efficacy. Subsequently, the impact of the methodological strategy on the experimental group was analyzed in comparison with the control group. The findings showed a significant difference between both groups, according to the Mann-Whitney U test (U=259.00) with a significance level of p-value =.01 < .05. It was concluded that this type of cooperative strategies, focused on the critical analysis of issues of public interest from a controversial perspective, are beneficial to strengthen students' confidence by actively participating in various dynamics of oral discussion, such as round tables, debates, forums and panels.